Aplikasi Pemantauan Akademik dan Non-Akademik Siswa Sekolah Dasar Berbasis Web dan Mobile - Hidayat, Rizki; Mardhiyyah, Rodhiyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Student learning assessment is an essential component of education as it measures competency achievement and supports the continuous development of learning strategies. At SDN 2 Bungko Lor, Cirebon, the management of academic and non-academic data is still carried out manually using printed report cards and Excel spreadsheets. This condition limits parents’ ability to monitor their children's learning progress, as results are only accessible at the end of each semester. This study aims to design and develop a Web- and Android-based Academic and Non-Academic Monitoring Application using the Waterfall method to simplify data management, improve information accessibility, and strengthen communication among schools, teachers, and parents. The system was developed using Vue.js for the web application, Flutter for the Android application, PHP as the back-end, and MySQL as the integrated database. The system design applied UML (Use Case, Activity, and Class Diagrams) to model workflows and data structures. The main features include multi-user login, management of grades and attendance as academic data, recording of student behavior as non-academic data, class schedules, and a two-way chat feature to support coordination between schools and parents. Testing using the Black Box method confirmed that all core functionalities operated properly. The implementation of this system provides a more structured presentation of information and enhances collaboration between schools and parents in monitoring students’ academic and non-academic development.